Синтез нового поданда, 1,8-бис(9’-карбазолил)-3,6-диоксаоктана - Кравченко, С. В. (НТУ "ХПИ", 2015)
Предложен метод синтеза нового подандного катализатора фазового переноса, содержащего две карбазолильные группы, стойкий к действию щелочей – 1,8-бис(9’-карбазолил)-3,6-диоксаоктана. Поданд аминного типа синтезирован взаимодействием 1,8-дибром-3,6-диоксаоктана с калиевой солью карбазола. Доочистка продукта от следов карбазола происходит при перекристаллизации из бензола. Структура 1,8-бис(9’-карбазолил)-3,6-диоксаоктана доказана с помощью данных ЯМР ¹Н, ¹³С-спектров, а также масс-спектров.

The main kind of phase transfer catalysts are crown-esters, cryptands, quarternary ammonia salts and podands. The podand kind of phase transfer catalysts is the most efficient for the organic chemistry technologies. The aim of this investigation is the syntheses of new podand which consists of two carbazole moiety and triethylenglygol chain. The synthesis of 1,8-bis(9’-carbazolyl)-3,6-dioxaoctane has been proposed. This containing two carbazolyl moiety podand is stable in the alkali media. The reaction of the synthesis is carried out in the 1,4-dioxane solution. Carbazole reacts with excess of potassium hydroxide in the boiling solvent in the presence of tetrabutyl ammonia bromide. Then the hot solution of potassium salt of carbazole is filtered off. Then the reaction of potassium salt of carbazole with 1,8-dibromo-3,6-dioxaoctane is carried out in 1,4-dioxane solution. After that the reaction mixture is cooled. The obtaining potassium bromide is filtered off. The 1,4-dioxane reaction solution is evaporated at reduced pressure. The residue is washed by water and then it is dried at reduced pressure. Then the resid ue is extracted by boiling tetrachlorocarbon. The extract is evaporated at reduced pressure yielding the technical product. The crude product yield is 77 %. The solid residue was crystallized from benzene or ethanol yielding the pure product. The additional quantity of the product is obtained by the column chromatography of the filtrate residue. The overall yield of pure 1,8-bis(9’-carbazolyl)-3,6-dioxaoctane is 54 %. The melting point of 1,8-bis(9’-carbazolyl)-3,6-dioxaoctane is 128–129 °С. The product structure has been confirmed by data of NMR ¹H-spectra, NMR ¹³C-spectra and mass-spectra.
The synthesis of new podand, 1,8-bis(9’-carbazolyl)-3,6-dioxaoctane
Keywords: катализатор; перенос фазовый; щелочь; соль калиевая; бензол; phase transfer; catalysts; carbazole